1935
DOI: 10.1021/ja01314a061
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Kinetics of the Permanganate—Oxalate Reaction. I. The Effect of Various Salts upon the Rate of Reaction1

Abstract: Since the classical work of Harcourt and Essona the kinetics of the reaction between permanganate and oxalate ions in acid solution have been studied by several investigator^.^^^^^ The development of a sound theory of kinetic salt effect by Bronsted6 offers another method of investigating the mechanism of this reaction. Lamersa has shown that a positive salt effect is found when the reaction occurs in the presence of relatively large concentrations of oxalate and of added manganous ion.A mechanism for the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1951
1951
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The formation of intermediates (C 2 O 4 •– and/or CO 2 •– ) in the title reaction is widely acknowledged, , but their fate is the source of much conjecture. Numerous researchers have proposed the reduction of manganese species (Mn III and/or Mn IV ) by radical intermediates. , Kinetic analysis with radical scavengers have suggested that such reactions do occur, but in recent discussions, , these pathways have been overlooked. Similarly, Perez-Benito et al reported autocatalysis in the reduction of oxalic acid by colloidal MnO 2 (formed in neutral solution), which they attributed to a pathway involving adsorption of both oxalic acid and [Mn II (C 2 O 4 )] on the particle surface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The formation of intermediates (C 2 O 4 •– and/or CO 2 •– ) in the title reaction is widely acknowledged, , but their fate is the source of much conjecture. Numerous researchers have proposed the reduction of manganese species (Mn III and/or Mn IV ) by radical intermediates. , Kinetic analysis with radical scavengers have suggested that such reactions do occur, but in recent discussions, , these pathways have been overlooked. Similarly, Perez-Benito et al reported autocatalysis in the reduction of oxalic acid by colloidal MnO 2 (formed in neutral solution), which they attributed to a pathway involving adsorption of both oxalic acid and [Mn II (C 2 O 4 )] on the particle surface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…which gives for the rate of carbon dioxide formation: While the differences in the exponents of the permanganate-and manganous-ion concentrations may reasonably be neglected, the dependence of rate on hydrogen-ion concentration is in disagreement with the experiments of Launer (85), Launer and Yost (87), and Duke (46). Fessenden and Redmon (49) have proposed another mechanism, but their scheme is in conflict with the radiochemical work, for although the scheme involves both Mn4+ and Mn3+ ions, the reaction would permit the spread of radioactivity from Mn2+ to .…”
Section: Mnc2oímentioning
confidence: 86%
“…Their scheme is very similar to that proposed by Launer and Yost (87). Fessenden and Redmon (49) have also studied the effect of various salts on the rate of the permanganateoxalate reaction. In the oxalate-concentration range in which their studies were made, they find the maximum rate of oxidation to be approximately inversely proportional to the oxalate concentration.…”
Section: Mnc2oímentioning
confidence: 99%
See 1 more Smart Citation
“…Consider a reaction mechanism somewhat modified from that proposed by Launer and Yost (30): 2MnOt-+ 3Mn(II) + 16H + ->5Mn(IV) +8H20 (rapid) (1) Mn(IV) + Mn(II) <=i2Mn(III) (rapid, reversible) (2) Mn(IV) + C204 Mn(III) + C02 + C02-(measurable) (3) Mn(IV) + C02--C02 + Mn(III) (rapid) (4) Mn(III) + 3C204--<=i [Mn(III)(C204)3]--(reversible) (5) Mn(III) + C204 -Mn(II) + C02 + C02_ (measurable) (6) Mn(III) + C02~-> Mn(II) + C02 (fairly rapid) (7) C02~+ 02 <=t02C02-(rapid, reversible) (…”
Section: Sodium Oxalatementioning
confidence: 99%